Tinjauan Literatur terkait Peran Aspek Etika Tenaga Medis dalam Penerapan Budaya Keselamatan Pasien di Rumah Sakit - Nurma Nurma; Arlin Adam; Andi Alim (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
Hospitals are healthcare facilities aimed at improving health recovery and maintenance. Patient safety is a top priority in hospitals, and it is related to issues of quality and image, ranging from cases of malpractice, negligence in patient care, discrimination against patients, to other criminal acts. To date, patient safety has not fully become an integral part of healthcare practices. This is reflected in the continued occurrence of ethical violations in the form of malpractice, discrimination, and other forms of behavior. Every healthcare profession has a code of ethics that serves as a guideline for professional behavior. The existence of a code of ethics should be the foundation for building a patient safety culture. Law Number 44 of 2009 concerning Hospitals explicitly states that patient safety is a top priority in healthcare. This study used a literature review method by examining various online scientific publication sources. The results of the literature search were then analyzed and processed to produce in-depth discussions and conclusions relevant to the research topic. The results of the study indicate that the implementation of a professional code of ethics by medical personnel plays a significant role in building a patient safety culture. This culture can only be realized if supported by an ethical organizational climate, open communication, and patient safety-oriented leadership. Therefore, professional ethics must be a core component of a hospital service system oriented toward patient safety. Furthermore, it is important to recognize that implementing a patient safety culture relies not only on medical personnel but also involves all elements within the hospital, including management, administrative staff, and other support personnel. Commitment from all parties to consistently implementing patient safety principles can strengthen the desired safety culture.